2022
DOI: 10.3390/polym14030636
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Textile Dye on Blended Cellulose Acetate Membranes

Abstract: This work aimed to investigate the degradation performance of natural cellulose acetate (CA) membranes filled with ZnO nanostructures. Photocatalytic degradation of reactive toxic dye methylene blue (MB) was studied as a model reaction using UV light. A CA membrane was previously casted and fabricated through the phase inversion processes and laboratory-synthesized ZnO microparticles as filler. The prepared membrane was characterized for pore size, ultrafiltration (UF) performance, porosity, morphology using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…These findings are consistent with those of previous studies [ 67 , 69 ]. Neat cellulose acetate-based films exhibited a moderate water contact angle value (WCA = 92.7°) due to the hydrophobicity of cellulose acetate [ 70 , 71 ]. The incorporation of hydrophobic Fe x O y -NPs enhanced the hydrophobicity of the cellulose acetate-based nanocomposite films by increasing the WCA to 105 °.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with those of previous studies [ 67 , 69 ]. Neat cellulose acetate-based films exhibited a moderate water contact angle value (WCA = 92.7°) due to the hydrophobicity of cellulose acetate [ 70 , 71 ]. The incorporation of hydrophobic Fe x O y -NPs enhanced the hydrophobicity of the cellulose acetate-based nanocomposite films by increasing the WCA to 105 °.…”
Section: Resultsmentioning
confidence: 99%
“…This value may confirm the effect of the polymer concentration on the hydrophilic behavior of a thin film [ 74 , 75 ]. In contrast, other studies have reported hydrophobic behaviors of CA-based films [ 76 , 77 ]. The hydrophobic behavior of CA-based neat film prepared at 2% ( w / v in acetone) was also reported in a previous study with the WCA ≈ 93° [ 78 ].…”
Section: Resultsmentioning
confidence: 82%
“…Some researchers found that CA with a degree of substitution (DS) greater than 1.5 could not be degraded by natural organisms, whereas others found that CA with a DS of 2.5 had limited value, owing to deterioration. The main mechanism for degradation is an initial deacetylation process involving chemical hydrolysis and acetyl esterases, which allows the degradation of the cellulose backbone [ 161 , 162 ]. The analysis shows that moisture in the soil caused cellulose acetate fibers to decay significantly, and after a few months, they were completely gone.…”
Section: Design For Degradationmentioning
confidence: 99%